Ganefo Sports Competition in Political Sports Contestation in Indonesia - Yulfiras Thariqi; Himawan Wismanadi; Nofulan Adiyani; Noortje Anita Kumaat (UNIVERSITAS NEGERI MAKASSAR, 2024)
Badminton has become one of the most popular sports in Indonesia, with impressive achievements in various international championships that have brought pride to the nation. However, it cannot be denied that political factors also influence the performance of Indonesian badminton athletes. This study aims to analyze the influence of politics on the sporting achievements of badminton in Indonesia. The methodology used is a literature study using several relevant research sources. The research results show that politics has a significant influence on the sporting achievements of badminton in Indonesia. Government policies related to athlete development and funding are crucial factors that determine the progress of this sport. The political role can also create instability in the broadcasting policies of sports on public broadcasting institutions, as well as becoming an obstacle in the development of badminton through corruption practices that affect the allocation of funds.